2022
DOI: 10.3389/fpubh.2022.992895
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trust in government on pandemic management on the compliance with voluntary COVID-19 vaccination policy among adolescents after social unrest in Hong Kong

Abstract: BackgroundThe launch of COVID-19 vaccines among students provides an opportunity to re-open schools safely. Nonetheless, under the voluntary vaccination policy, the lack of trust in government since the unprecedented massive social unrest in Hong Kong may hinder the vaccination progress. This study aims to assess the impact of trust in government regarding pandemic management on the willingness, uptake, and intention of COVID-19 vaccination among students in Hong Kong.MethodsBased on maximum variation sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…This study highlights that individuals with a higher level of trust in information from the government were more likely to receive the first dose vaccine early. This result is similar to several local studies [ 52 , 53 , 54 ] and reveals that people learn about the pandemic and take action to prevent infection not only considering the content and quality of the information but also their levels of trust in information from their government [ 25 , 55 ]. We also found that the standardized indirect/mediated effects of trust in information from the government on the associations between two subdomains of CHL and first dose vaccination were negative.…”
Section: Discussionsupporting
confidence: 87%
“…This study highlights that individuals with a higher level of trust in information from the government were more likely to receive the first dose vaccine early. This result is similar to several local studies [ 52 , 53 , 54 ] and reveals that people learn about the pandemic and take action to prevent infection not only considering the content and quality of the information but also their levels of trust in information from their government [ 25 , 55 ]. We also found that the standardized indirect/mediated effects of trust in information from the government on the associations between two subdomains of CHL and first dose vaccination were negative.…”
Section: Discussionsupporting
confidence: 87%
“…Data were collected from a purposive sample of 12 secondary schools of different socioeconomic background (see the socioeconomic classifications in Supplementary Table 1 ) in Hong Kong via online survey between September and October 2021 ( 22 ). Invitation letters were sent to members of the Hong Kong Association of the Heads of Secondary Schools (established by dedicated secondary school principals with a vision to enhance professionalism and the understanding of education in secondary schools) to recruit all Secondary 3 students enrolled to each participating school (equivalent to Grade 9 in the United States or Year 10 in the United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these key factors, an individual’s views and attitudes towards society have been highlighted as correlates of vaccination in an increasing number of studies. Notably, higher levels of social capital [ 10 , 11 , 12 ] and trust in government [ 13 , 14 , 15 ] are found to be in favor of vaccination in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon previous studies [ 10 , 11 , 12 , 13 , 14 , 15 ], we examined how general trust in others, trust in government, and interaction with neighbors affect an individual’s decisions on vaccine uptake. General trust in others is a key element of social capital, which is defined as the quality of relationships among community members [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation